2016
DOI: 10.1094/mpmi-10-15-0234-r
|View full text |Cite
|
Sign up to set email alerts
|

Strigolactone-Induced Putative Secreted Protein 1 Is Required for the Establishment of Symbiosis by the Arbuscular Mycorrhizal Fungus Rhizophagus irregularis

Abstract: Arbuscular mycorrhizal (AM) symbiosis is the most widespread association between plants and fungi. To provide novel insights into the molecular mechanisms of AM symbiosis, we screened and investigated genes of the AM fungus Rhizophagus irregularis that contribute to the infection of host plants. R. irregularis genes involved in the infection were explored by RNA-sequencing (RNA-seq) analysis. One of the identified genes was then characterized by a reverse genetic approach using host-induced gene silencing (HIG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
133
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(133 citation statements)
references
References 64 publications
0
133
0
Order By: Relevance
“…1b, f, Supplementary Data 6). AMF has developed a unique signal pathway for symbiosis (e.g., establishments of symbiosis with pathways via SIS1 41 and lyso-phosphatidylcholine 42 ). This inflation of signaling-related genes may have led the development of a complex signaling pathway in AMF.…”
Section: Resultsmentioning
confidence: 99%
“…1b, f, Supplementary Data 6). AMF has developed a unique signal pathway for symbiosis (e.g., establishments of symbiosis with pathways via SIS1 41 and lyso-phosphatidylcholine 42 ). This inflation of signaling-related genes may have led the development of a complex signaling pathway in AMF.…”
Section: Resultsmentioning
confidence: 99%
“…The symbiosis‐upregulated genes of ERM fungi include a cluster of taxonomically restricted genes specific to each ERM fungal species that contain a high proportion of effector‐like MiSSPs. Characterized MiSSPs dampen plant defense reactions in AM and ECM symbioses (Kloppholz et al ., ; Plett & Martin, ; Tsuzuki et al ., ). The percentage of MiSSPs (10–20% of total SSPs) in ERM falls in a range similar to that found for ECM fungi (4–21%; Kohler et al ., ) and for the AM fungus R. irregularis (19%, Tisserant et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Some SSPs with a similar activity were also described by functional analyses in mutualistic plant–fungal association (Kloppholz et al, 2011; Plett et al, 2011; Tsuzuki et al, 2016). More recently, a comparative in silico analysis revealed that many SSPs were shared by both arbuscular mycorrhizal fungi Rhizophagus clarus and Rhizophagus irregularis , supporting the role of secreted peptides in mycorrhizal associations (Sędzielewska Toro and Brachmann, 2016).…”
Section: Fungal Secretomes Support the Saprotrophic—ecm Fungi Continuummentioning
confidence: 71%